Thyroid hormones and glycaemic indices in euthyroid, hyperthyroid, hypothyroid, all type 2 diabetics and non-diabetic subjects - Isong, Idongesit Kokoabasi (2023)
FPG and HbAlc were positively correlated in all type 2 diabetic group (r = 0.211, P = 0.007) and in the hypothyroid type 2 diabetic subjects (r = 0.382, P = 0.011) and hyperthyroid groups (r = 0.295, P = 0.011). FPG also correlated positively with C-pep in all type diabetics (r = 0.224, P = 0.004) and hyperthyroid type 2 subjects (r = 0.481, P = < 0.001). There was no significant correlation between FPG and HbAlc or C-pep in the other group (Table 1). There were no significant correlations between FPG and all the thyroid hormones.